Mummy berry pseudosclerotia survive for several years - Pscheidt, J. W.; Bassinette, J. P.; Warneke, B. (Frontiers in Plant Science, 2023)
Organic blueberry production in the PNW has many challenges, including diseases like mummy berry caused by the fungus Monilinia vaccinii-corymbosi (Reade) Honey. Management recommendations focus on reducing overwintering pseudosclerotia, however, it is unknown how long they survive. Based on qualitative observations pseudosclerotia are hypothesized to survive multiple years after contact with the soil surface. The development of apothecia from M. vacciniicorymbosi pseudosclerotia was evaluated over multiple years at a location without a history of blueberry production. A total of 1,000 pseudosclerotia were placed on field soil plots in 2018 and replicated eight times. Another 100 pseudosclerotia were placed in wire corrals on field soil and replicated fifteen times. Plots and corrals were regularly examined each spring for the emergence of apothecia. The pseudosclerotia were able to survive, germinate, and produce apothecia for up to five years after their placement. Very few pseudosclerotia produced apothecia in any year, varying from 0 to 18 at any observed time. Pieces of partial or whole pseudosclerotia were observed for up to three years after placement. Our study shows that a pseudosclerotial "seed bank" exists under blueberry bushes, necessitating a long-term implementation of mummy berry cultural management tactics.